Growing Insights and Youth Knowledge in the NFT Hydraulic Application (Nutrient Film Technique) - Johan Andri Pratama; Alfian Hamdani; Aryanda Tata Permana (Kontribusia : Research Dissemination for Community Development, 2019)
The more rapid growth of technology allows humans to work effectively and efficiently. Technology proves the way humans change patterns of significant social change, from those that initially used human power to machines. The way humans use machines is inseparable from the ways and techniques of its use which are effective and efficient. One of the technologies used is the technology of crop cultivation without using soil as a planting medium. The technology introduced is hydroponics. Hydroponics as a way of farming is an approach that has several advantages, namely the use of agricultural land that is not extensive, and the system is not too complicated. The introduction of this technology aims to provide insight and knowledge to the public about the technology of crop cultivation in addition to conventional farming systems. This activity was carried out in Rayung gumuk Village, Glagah District, Lamongan Regency. The hydroponic system that we introduce is the NFT hydroponic system (Nutrient Film Technique). The goal is because the hydroponic system is easily applied and has several significant advantages. The first method of implementation is socialization.This is done to find out the extent to which people's insights and knowledge about hydroponics and the interests and interests of the community towards hydroponic using the NFT system. Moreover, the second is training. It aims to provide techniques and methods for assembling NFT hydroponic installations. From the results of our activities, the community's response to hydroponics is still minimal because some of them still consider hydroponic use too costly and their disinterest in agriculture.